Factors Associated with Chronic Kidney Insufficiency Stage: A Cross-Sectional Study - Siti Fadlilah; Nazwar Hamdani Rahil; Uswatun Khasanah; Santi Damayanti; Ariyanto Nugroho; Fika Lilik Indrawati (Media Kesehatan Masyarakat Indonesia, 2023)
Chronic Kidney Insufficiency (CKI) is a kidney disorder that occurs for at least three months and can become a chronic kidney disease. Many risk factors can cause CKI related to individual characteristics and lifestyle. The purpose is to determine the relationship between age, gender, diabetes mellitus, hypertension, smoking, and consumption of energy supplements with CKI stage in a selected hospital in Indonesia. This research was an analytic observational quantitative with a cross-sectional design. The number of samples was 325 patients using the accidental sampling technique. The instrument used creatinine results and Glomerular Filtration Rate calculations based on laboratory tests, questionnaires, and observation sheets. Bivariate analysis with Chi-Square. Most of the respondents in the CKI stage V (38.8%), late elderly (35.4%), male (56.9%) had a history of diabetes mellitus (55.4%), hypertension (67.7%), did not smoke (78.5%), and does not consume energy supplements (62.5%). Bivariate analysis showed a meaningful relationship between age (X2=8.52, p=0.019), history smoking behaviour (X2=7.12, p=0.026), diabetes mellitus (X2=4.39, p=0.037, and hypertension (X2=7.99, p=0.026) with CKI stage. Age, smoking behaviour, history of diabetes mellitus, and hypertension were associated with the CKI stage.